Campur Kode dalam Proses Pembelajaran Bahasa Indonesia di SMA Negeri 1 Rantepao - Resnita Dewi (Jurnal Ilmiah Wahana Pendidikan, 2020)
This research aims to describe the form of the use of code interfering in the Indonesian language learning process at SMA Negeri 1 Rantepao, North Toraja.The research is a qualitative descriptive research type. The Data in this research is the code of mixed teachers and students in the learning process of Bahasa Indonesia class XI language SMA Negeri 1 Rantepao. Data is collected with observation, record, and record techniques.The form of code is derived from the Indonesian language learning process in SMA Negeri 1 Rantepao in the form of insertion of elements in the form of (1) words, (2) phrases, and (3) sentences. Mix the code found aimed at knowing, informing, asserting, as well as explaining something.